Nursing of a patient with cervical spondylosis intervened by Huolong cupping combined with auricular acupoint pressing therapy (火龙罐联合耳穴压豆干预颈椎病1例护理体会) - ZHANG Chengjiao (张承姣); WANG Qi (汪琦); LUO Lili (罗黎黎) (中西医结合护理)
This paper investigates the effect of Huolong cupping combined with auricular acupoint pressing therapy on pain, dizziness and insomnia symptoms in a patient with cervical spondylosis, and summarize related nursing measures. Based on the comprehensive nursing assessment and syndrome differentiation by Traditional Chinese Medicine, the Huolong cupping combined with auricular acupoint pressing therapy was applied to relieve the pain, dizziness and insomnia symptoms caused by cervical spondylosis. Additionally, routing nursing, psychological care, dietary guidance and functional exercise were carried out to improve patient’s quality of life during treatment. (本文总结采用火龙罐综合灸联合耳穴压豆干预1例颈椎病患者疼痛、眩晕、不寐等临床症状的护理经验。在完善护理评估的基础上, 基于中医辨证理论指导, 开展火龙罐综合灸联合耳穴压豆技术干预, 同时完善常规护理、心理护理、饮食护理、功能锻炼等护理措施, 提高患者舒适度, 缓解焦虑情绪, 改善睡眠质量和生活质量。)